(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف البحث إلى قياس دور أنشطة اللعب الجماعية في تنمية الشخصية القيادية لدى طفل الروضة (5–6) سنوات, لذلك قامت الباحثة بتصميم اختبار الشخصية القيادية اعتماداً على مفهوم القيادة ونظرياتها في المراجع العلمية وعلى سمات الشخصية القيادية الواجب توافرها, كما صممت مجموعةَ من الألعاب الجماعية التي تهدف إلى تنمية مهارات الشخصية القيادية. بعد ذلك وبهدف التأكد من صلاحية الاختبار, تم تحكيمه من قبل مجموعةِ من السادة أعضاء الهيئة التدريسية في كلية التربية بجامعة دمشق, إذ رأى 83٪ منهم قدرة الاختبار على قياس مقومات الشخصية القيادية لدى الأطفال, كما تم التأكد من ثبات الاختبار بطريقة ألفا كرونباخ على العينة الاستطلاعية، وحصل الاختبار على معامل ثبات قدره (90٪). يتكون مجتمع البحث من أطفال الرياض في مدينة دمشق، وقد تم تطبيق الاختبار في روضة الرائد الخاصة البالغ عدد أطفالها120 طفلاً وطفلةً, إذ تم سحب عينةٍ عشوائيةٍ من أطفالها, شملت 52 طفلاً من الفئة العمرية (5 - 6) سنوات، وقسِّمت العينة إلى مجموعتين: ضابطة (26) طفلاً, وتجريبية (26) طفلاً. وقد أُخضِعَت المجموعتان لاختبار الشخصية القيادية في الاختبار القبلي، وبعد ذلك طُبِقَت مجموعة الألعاب الجماعية على المجموعة التجريبية لمدة ثلاثة أسابيع متتالية فقط ، دون أن تتعرض المجموعة الضابطة لأي تغيير، إذ أُبقيَت على الطرائق التقليدية المتبعة سابقاً، وبعد انتهاء فترة التطبيق أُخضِعَتا إلى الاختبار البعدي. لقد توصلت الباحثة إلى ضعف قدرة الطريقة التقليدية المستخدمة في تعليم أطفال الرياض, مقارنة بكفاءة وفعالية طريقة استخدام أنشطة اللعب الجماعية, فيما يتعلق بإكساب وتعليم الطفل مهارات الشخصية القيادية. The research aims to measure the role of collective play activities in the development of personal leadership in child kindergarten (5-6 years), so the researcher designed personal leadership test based on the concept of leadership and theories in the scientific literature and on the personality traits of leadership that must be met, and designed a set of collective games which aims to develop personal leadership skills. After that, and in order to ensure the validity of the test, it was refereed by a group of the members of the College of Education at the University of Damascus, 83% of them saw its ability to measure the elements of personal leadership by children, we have also been making sure the stability of the test in a manner alpha Cronbach on the sample reconnaissance, and won the test on the stability factor of (90%). The research community consists of the children of kindergarten in the city of Damascus. The test has been applied to the children of Leading Private Kindergarten which has 120 boys and girls, the sample of children was withdrawn randomly , including 52 children in the age group (5-6 years), and divided the sample into two groups: officer (26) children, and experimental (26) children. The two groups were subjected to personal leadership test in the pre-test, and then the collective games were applied on the experimental group for a period of three consecutive weeks only, without being exposed to any change, as it kept the traditional methods used previously, and after the end of the application period we applied the post-test. The researcher has found that the traditional teaching methods have lesser effect than the modern methods which use the collective playing activities to transport knowledge and skills of the personality of Leadership to the child.